Non-grasping en bloc mediastinal lymphadenectomy in videoassisted thoracoscopic lobectomy for lung cancer - Kikuchi, Hirotoshi; Takeuchi, Hiroya (Journal of Thoracic Disease, 2018)
Video-assisted thoracoscopic surgery (VATS) lobectomy has been developed as a minimally invasive surgery since it was first reported in 1992 (1). The feasibility, safety, efficacy, and oncologic equivalence of VATS lobectomy have been investigated in numerous studies including randomized controlled trials. Although there remain some controversies in VATS lobectomy with mediastinal lymphadenectomy (2-4), it is widely performed, and National Comprehensive Cancer Network (NCCN) guidelines for non-small cell lung cancer (NSCLC) and the American College of Chest Physicians (ACCP) guidelines recommend VATS lobectomy for the treatment of early stage lung cancers (5,6).